Impact of electronic Word Of Mouth (eWOM) on Consumer Behaviour - Lili Marlinah; Fahri Eka Oktora; Ady Kurnia; Ela Elliyana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
Word-of-mouth (WOM) is one of the most influential sources of information transmission. However, its effectiveness is limited to social contact. With the rise of social commerce, electronic word-of-mouth (eWOM) has become an important reference for information users. However, the quality of information communicated by eWOM across major platforms is uneven, which seriously affects users' trust in eWOM and platform reputation. Therefore, this study provides an overview of the influence of eWOM on consumer decision-making and purchasing behavior, as well as eWOM interest, from an information quality perspective. The literature review method was used, with Scopus indexed articles using the eWOM keyword taken from the database using Harzing's Publish or Perish (PoP). The articles were selected based on their Google Scholar rating from 1 to 20